Physical Therapy–Based Exercise Protocol for Cancer Patients: Evaluating Outcomes for Cardiopulmonary Performance and Cancer‐Related Fatigue. Issue 11 (16th April 2019) - Hutchison, Nancy A.; Deval, Nikita; Rabusch, Stacey; Rich, Holly; Kelley, Tom; Flinn, Nancy; Banerji, Nilanjana
Abstract : Background: Studies have shown that rehabilitation and fitness throughout cancer treatment interventions have been linked to improved outcomes for morbidity and mortality of cancer patients. This study serves to detail the efficacy of the Cancer Rehabilitation Physical Therapy Fitness and Debility (Ca PT) Program in cancer patients. Objective: To describe the clinical population of cancer patients referred to the Ca PT Program and evaluate the efficacy of the program's therapy protocol in improving cardiopulmonary performance and cancer‐related fatigue and pain. Design: Retrospective study. Setting: Outpatient clinics. Patients: One hundred two adults who had been referred from a variety of referral sources and supervised individualized exercise programs. Methods: Participation in the Ca PT Program. Main Outcome Measurements: The primary outcome measure was a change in baseline‐to‐discharge scores in the 6‐Minute Walk Test (6MWT), a cardiopulmonary performance measure. The secondary measures were changes in baseline‐to‐discharge scores of cancer‐related fatigue and general pain, measured by patient self‐report using a visual analogue scale. Results: 6MWT values were significantly higher at discharge (mean 523 yards) than at baseline (mean 436), ( P  < .001, r = 0.57). Ninety‐two percent of cases showed improvement and 58% of cases had a change on the 6MWT that met threshold for minimal important difference. Quality of life factors, fatigue ( P  < .001) and pain ( P  < .001) also significantly improved. Conclusions: The results indicate the Ca PT Program yields significant improvement in cardiovascular fitness, fatigue, and pain in people with cancer history. Personalized physical therapy fitness programs for individuals recovering from cancer treatment should be a standard component of cancer intervention. Level of Evidence: III